Systemic Determinants of the Scope of Application of the Legal Definition of „Beneficiary” under the Cohesion Policy - Talaga, Robert (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The general framework for spending the EU budget, adopted by authorized institutions, is to contribute to the implementation of the strategic development goals set by individual Member States. It is up to national legislators to develop and specify such regulations, who remain authorized to issue relevant normative acts in accordance with the applicable institutional and procedural autonomy (Galetta 2010). In the Polish legal system, the legislator adopts appropriate statutory regulations for each successive programming period of the EU budget. Under the cohesion a co-financing agreement and on the basis of an administrative decision has been retained. So far, the concept introduced in this way had different meanings depending on the content of the provisions formulated by the EU legislator and the national legislator. Therefore, it was necessary to take into account the definition of „beneficiary” contained in both separate provisions of national law and European law, often also taking into account the specificity of the purpose of individual funds. The legal definitions introduced in this respect had a specific scope of validity. However, it was not always identical to the intentions of the national legislator. At the same time, there were systemic factors which, on the one hand, extended the scope of application of the introduced legal definitions, and, on the other hand, limited them.